Study of the mixture formation processes inside a modern direct-injection gasoline engine - Koch, Petra; Löffler, Mario; Wensing, Michael; Leipertz, Alfred (International Journal of Engine Research, 2010)
The combustion process inside a direct injection spark ignition engine with charge stratification is a very complex process with a large number of variables existing for the definition of the engine characterization map. In this work, two different tracer-based laser-induced fluorescence techniques were applied to analyse the charge motion during the mixing process. For two different operation points with and without a complex in-cylinder flowfield, the two-line excitation LIF technique was applied for temperature and residual gas fraction imaging, and the FARLIF technique for fuel/air ratio imaging. It was found that the mixing of air and residual gas was very fast, and hence no inhomogeneities were found at ignition time. For the mixture preparation process, the swirl makes it difficult to position the fuel vapour cloud near the spark plug at ignition. As a solution to overcome this, a double-injection strategy was applied. With careful parameter choice, depending on the second injection mass and timing, the desired charge situation could be achieved. © Authors 2010.
Created from Fastlane, Scopus look-up
Keywords: DISI; fuel/air ratio; mixture formation; optical engine; residual gas; tracer-LIF